Features of severe course of tropical malaria with secondary diseases caused by Klebsiella pneumonia (clinical case) - R. B. Oganyan; I. V. Roganova; A. V. Lyubushkina; G. R. Davlekamova; D. Yu. Konstantinov; V. A. Nikonorov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2025)
Relevance. Imported malaria cases in the Russian Federation are detected annually. In the absence or delayed treatment it can lead to patients´ complications and death. The aim of the work is to present and analyze a fatal tropical malaria clinical case with secondary diseases caused by Klebsiella pneumoniae. Materials and methods. The work was carried out on the basis of the clinic and the Department of Infectious Diseases with Epidemiology of Samara State Medical University. A clinical case of tropical malaria severe course in a patient on the 18th disease day admitted in a malarial algid state. Results. Sepsis, pneumonia, and meningitis were found in a patient with tropical malaria. Klebsiella pneumoniae was isolated from the patient's biomaterials. The development of secondary diseases caused by Klebsiella pneumoniae contributed to the patient's condition worsening and the multiple organ failure progression. The late etiotropic treatment led to the multiple organ failure and patient´ death. Conclusions. The clinical example demonstrates the vital need for the epidemiological history correct interpretation, malaria early diagnosis and treatment.